2020
DOI: 10.3390/pr9010033
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Convolutional and Recurrent Neural Network for Quality Prediction of Continuous Casting Slabs

Abstract: Quality prediction in the continuous casting process is of great significance to the quality improvement of casting slabs. Due to the uncertainty and nonlinear relationship between the quality of continuous casting slabs (CCSs) and various factors, reliable prediction of CCS quality poses a challenge to the steel industry. However, traditional prediction models based on domain knowledge and expertise are difficult to adapt to the changes in multiple operating conditions and raw materials from various enterpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Continuous casting process has signific effect of the overall quality of the steel products [15]. In [16], the quality of continuous casting slabs was predicted using a time series classification. Mold level fluctuations were measured at 0.5-s intervals, and the data were combined with inspection machine data.…”
Section: Related Workmentioning
confidence: 99%
“…Continuous casting process has signific effect of the overall quality of the steel products [15]. In [16], the quality of continuous casting slabs was predicted using a time series classification. Mold level fluctuations were measured at 0.5-s intervals, and the data were combined with inspection machine data.…”
Section: Related Workmentioning
confidence: 99%
“…Compared with the classical decision tree, and SVM, the results showed that the improved random forest model could deal with the negative effects of the class imbalance problem in accordance with the recall index. Wu et al [24] created a framework with multiscale convolutional and recurrent neural networks for reliable CC slab quality prediction. Moreover, they generated different category distributions based on the random undersampling method to alleviate the impact of skewed data distribution in the face of natural imbalances in industrial data.…”
Section: Related Workmentioning
confidence: 99%
“…When this hybrid PSO-SVM-based model with RBF kernel function is tested on an experimental dataset, the coefficient of determination and average width are equal to 0.98 and 0.97, respectively. Wu et al [71] suggested a novel multiscale convolutional and recurrent neural network MCRNN architecture for which the input is converted at various scales and frequencies, recording both long-term patterns and short-term shifts in time series. The suggested system outperforms traditional time series classification approaches with improved feature representation.…”
Section: Steelmentioning
confidence: 99%